International Financial Reporting Standards: Theoretical Aspects - Victoria GANEA; Iulita BARCA; Mihaela-Ionela STANCIUC (SOCOLIUC); Anamaria MACOVEI (Communications of International Proceedings, 2021)
In this paper we aimed to analyse the International Financial Reporting Standards, which involves the description of the theoretical aspects and the practical importance of the application of the IFRS. Books and specialized articles in Romanian and foreign literature, legislative acts (laws and other national and European rules on the issue), official papers, and specialized websites used as databases to collect information about IFRS, IASB, IASCF, IAS, GAAP, IFRIC, and SIC. As a result, we proposed that our research be presented in a paper with a logical structure, with concise but well-argued information about IFRS, the importance of their application and offering this study to those interested in the field.
Keywords: International Financial Reporting Standards (IFRS); International Accounting Standards Board (IASB); International Accounting Standards (IAS); IFRS advantages/disadvantages.